Missing links. - Brown, Andrew (New Statesman, 1999)
The writer compares free computer software to Microsoft's expensive commercial software. He describes his own experience using various free software products on his UNIX operating system and some of the difficulties he experienced. He points out that Microsoft software conceals all the complexity involved in performing tasks on a computer. He decides that the boring reliability of the fact that almost everything within the Microsoft universe works together in the same way merits paying a lot of money for it.